DRUG ERADICATION AMONG THE YOUTH GENERATION - Muhammad Ihsan; M. Nazaruddin; Nirzalin Nirzalin; Fajri M. Kasim (Master Program of Sociology, Universitas Malikussaleh,, 2022)
This study observes social phenomena that occur in the people of Gampong Mon Geudong, Banda Sakti District, Lhokseumawe City, Aceh Province . This gampong was chosen because it is one of the gampongs known for its high drug circulation and drive in Lhokseumawe City, and finally a movement that is aware of the dangers of drugs has formed and formed the B-DAME organization which aims to overcome the problem of drug abuse in Gampong Mon Geudong. From the results of the study it was found that many young people were already trapped in the drug trap. The results of other studies found that the community care model incorporated in the B-Dame organization was effective in reducing drug and drug trafficking in Gampong Mon Geudong. The suggestion from this research is that the government completes the model that has been developed by the Mon Geudong community into a model implemented by various other gampongs so that the drug problem will slowly but surely be overcome later.